How Good Mathematical Critical Thinking Skills of Elementary School Student? The Case on Fraction Material - Nurlela, Euis; Hendriana, Heris; Supriatna, Tatang; Fitriani, Nelly (IKIP Siliwangi, 2025)
Critical mathematical thinking skills are fundamental abilities that students must develop to succeed in mathematics. In learning mathematics on fraction material, the critical mathematical thinking skills of grade V students at Gununghalu 1 Elementary School are not yet optimal. This study seeks to assess the essential mathematical thinking skills of fifth-grade students. The participants in this study consisted of 51 fifth-grade elementary school students from Ciranjang during the 2023/2024 academic year. The object of this research is students' mathematical critical thinking skills, efforts made to develop mathematical critical thinking skills, and obstacles faced in efforts to improve mathematical critical thinking skills. This research method is descriptive quantitative. The data collection techniques used were observation, interview and test. The instrument used to obtain the data in this study is a matter of description test, which amounted to 5 questions. The study revealed that fifth grade students demonstrated an average critical thinking ability of 51%, which falls into the low category. Among the various indicators assessed, the highest score was seen in the analysis of statements, reaching 76%, while the lowest score was in the evaluation of the truth of statements, which stood at just 26%. From this analysis, we can conclude that the mathematical critical thinking skills of fifth grade elementary school students remain at a low level